Analysis of Mortality Risk Factors in Children with Epidural Hematoma (EDH) - Nafira, Amodya Dahayu; Makkiyah, Feda Anisah (The SDGS Forum Communication, 2024)
Head injuries hold the third position among all injury categories in Indonesia, with the highest number of cases occurring in children. Approximately 2% of all head injury cases are epidural hematomas (EDH). The majority of these epidural hematoma cases are caused by head trauma such as accidents, falls, collisions, or other physical assaults leading to traumatic mechanisms. Additionally, EDH can also be caused by non-traumatic processes such as infection/abscess, vascular malformations, tumors, and coagulopathy disorders. Epidural hematoma has a relatively favorable prognosis, yet there are several factors that contribute to a worsened prognosis. This study aims to examine of several research articles outlining the factors contributing to mortality in pediatric EDH cases. The method used is a literature review technique utilizing scholarly databases meeting specific inclusion criteria. The study found that the preoperative GCS, preoperative treatment time interval, operative treatment, and pupillary abnormalities are some of the factors that can impact patient outcomes, including mortality rates, in pediatric EDH cases. Subsequent research is expected to delve deeper on the outcomes of patients undergoing surgical and conservative interventions to address mortality incidents in pediatric EDH.